Analysis of offensive transitions of Barcelona based on the initial penetration after the ball recovery - Papadopoulos, S.; Papadimitriou, K.; Ispirlidis, I.; Papadopoulos, D.; Konstantinidou, X. (SportMont, 2023)
Coaches and analysts alike agree that offensive transitions are very important in modern football. However, only few studies have analyzed offensive transitions in depth. The aim of this study was to analyze the effect of initial penetration on the tactical elements of offensive transitions of Barcelona during the period 2018-19. The sample included 1164 offensive transitions (605 with penetration and 559 without penetration), from 37 matches. The phases were recorded using SportScout analysis software. The parameters of the study were: outcome of attack, match location, quality of opposition, zone of ball recovery, type of ball recovery, initial opponent number, players in possession, type of attack, duration of attack, time frame of attack and match status. The statistical processing of the data was done with the Crosstabs analysis and the Chi-square significance test. The results showed that the tactical characteristics of Barcelona`s offensive transitions were significantly influenced by the initial penetration of play, with the exception of zone of ball recovery and quality of opposition parameters. In conclusion, it seems that the profile of Barcelona`s offensive transitions is influenced by the initial penetration. Also, the findings on quality of opposition suggest that Barcelona utilizes a similar play-style, regardless of opposition. Finally, the fact that offensive transitions that had penetration were almost equal to those that had no penetration, confirms that Barcelona didn`t always try to attack, as soon as they recovered possession, but often chose to complete more passes, aiming to develop its attacking play with more patience and less risk.